Eventos geológicos e climáticos influenciando o padrão filogeográfico de aves na América do Sul: enfoque em Amazona (Psittacidae) e dendrocolaptes ( dendrocolaptidae) - Rocha, Amanda Vaz (2012)
During the wet periods of the Quaternary the existence of faunistic corridors along the Chaco were proposed,which allowed the contact between the forest areas of Brazil and Argentina currently separated by this biome. Amazona tucumana and Amazona pretrei are considered allospecies that occurin Yungas forests and Araucaria forests, respectively. The understanding of speciation process of this lineage might contribute to comprehension of the influence of these corridors on the biogeography of birds of South America.Thus, this study aims to evaluate the influence of climatic and geological processes in the formation of these two species of parrots.Considering also that these two species were classified as vulnerable by IUCN, the study of the speciation process may provide subsidies for conservation. The genetic relationship between haplotypes and demographic processes were investigated based on a segment of 491 base pairs of the mitochondrial gene cytochrome oxidase I (COI).. In addition, weestimated the divergence time between populations of these species based on the theory of coalescence.The variability and average genetic distance in A. pretrei are higher than in A. tucumana.There was no evidence for any expansion of the species population.The divergence of these species must have occurred in the absence of gene flow for at least one million years ago.Based on data divergence is possible to propose that the lineage A. tucumana / pretreihas appeared in southern Brazil.Possibly the ancestral lineage used the existing forest corridors along the Chaco during the Pleistocene and occupied the Yungas forests.Data of genetic variability, support the current status of vulnerable to Amazona tucumana.